2019
DOI: 10.1108/ijbm-03-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Subjective financial knowledge, prudent behaviour and income

Abstract: Purpose The purpose of this paper is to study how subjective and objective knowledge of finance, behaviour in managing personal finances and socio-economic status affect financial well-being. Design/methodology/approach The financial well-being score is constructed in quantitative financial literacy survey data from Estonia as the arithmetic mean of four statements on a five-point scale. Four hypotheses are tested in multiple regression analysis. Findings Subjective knowledge has a stronger relation with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 42 publications
(64 reference statements)
8
89
1
1
Order By: Relevance
“…This approach is more suitable for measuring personal phenomena such as financial wellbeing. Previous studies, such as research conducted by Shim [11] attempt to explain financial behavior that affects a person's subjective assessment of an individual's financial well-being by emphasizing socio-economic roles; such as gender, age, income, education level, and marital status [12], financial knowledge [13], and financial inclusion [14].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is more suitable for measuring personal phenomena such as financial wellbeing. Previous studies, such as research conducted by Shim [11] attempt to explain financial behavior that affects a person's subjective assessment of an individual's financial well-being by emphasizing socio-economic roles; such as gender, age, income, education level, and marital status [12], financial knowledge [13], and financial inclusion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral finance theory relies on how the thinking process and cognitive errors impact investor choice and prices of the stock exchange (Dam, 2017). Investors do not follow the rational models of investment which are assumed in the theory of efficient markets and there exist significant variations in the behavior of investors (Wärneryd, 2001; Riitsalu and Murakas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that subjective financial knowledge has a positive relationship with financial well-being (Riitsalu and Murakas, 2019;Woodyard, 2013); financial behavior (Allgood and Walstad, 2013;Deenanath et al, 2019;Hilgert et al, 2003;Robb and Woodyard, 2011;Sivaramakrishnan et al, 2017;Seay and Robb, 2013;Tang and Baker, 2016;Xiao et al, 2014); and financial decisions (Khan et al, 2017). Even though previous studies have indicated that both objective and subjective financial knowledge are important to financial behavior to which they contribute different roles, several studies have revealed that subjective financial knowledge is more adequate for explaining financial decisions and behaviors than objective financial knowledge (Robb and Woodyard, 2011).…”
Section: Subjective Financial Knowledgementioning
confidence: 99%